Choice of Root Canal Irrigants by General Dental Practitioners of Tamilnadu- a Questionnaire Study - Dr. A. Jayasenthil (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Aim To find out the choice of root canal irrigant by general dental practitioners Methodology A questionnaire consisting of 20 questions were randomly distributed to 500 dental practitioners in Tamilnadu. The results were then analyzed and tabulated. Results It was found in the study that mostly dental practitioners prefer normal saline combined with sodium hypochlorite as primary irrigant. Conclusion Saline is the primary choice of irrigant in root canal procedures. It is necessary for the dental practitioners to update the knowledge of recent root canal irrigants with their uses.